Scumbags!: an ethnography of the interactions between street-based youth and police officers - Ilan, Jonathan (Policing and society, 2018)
The interactions between young, disadvantaged, urban men and the rank-and-file officers who police them should be understood as layered structural, cultural and emotional phenomena. Using data from a multi-dimensional ethnographic project, this paper demonstrates that structural issues manifest in cultural scripts which place both groups in confrontation with each other. Within a tightly bound geographic district, competitiveness between them can be animated by intense emotionality. Frustration, humiliation, disdain and the potential for elation push both parties into behaviours that cannot be understood through discretion and confidence models of decision-making alone. Ultimately, through recognising how questions of inclusion/exclusion play out in simultaneously structural, cultural and emotive ways, the problems generated by negative interactions between the two groups might be meaningfully understood.